Postcolonial studies across the disciplines - Gohrisch, Jana, 1962-; Grünkemeier, Ellen (Cross/cultures, 2013)
Bringing together contributions from various disciplines and academic fields, this collection engages in interdisciplinary dialogue on postcolonial issues. Covering African, anglophone, Romance, and New-World themes, linguistic, literary, and cultural studies, and historiography, music, art history, and textile studies, the volume raises questions of (inter)disciplinarity, methodology, and entangled histories. The essays focus on the representation of slavery in the transatlantic world (the USA, Jamaica, Haiti, and the wider Caribbean, West Africa, and the UK). Drawing on a range of historical.